The impact of private and independent colleges on the education system in Zimbabwe: the case of Gweru urban high schools - Mangwaya, Ezron; Ndlovu, Emily; Manyumwa, C. (Global Institute for Research & Education, 2016)
Education systems in many countries are run by national governments. When the formal education system provided by the government cannot cope with demand for education by learners then alternative educational avenues are explored. This study explores the impact that private and independent colleges have made in the education system in Zimbabwe. The study proffers a view of private and independent colleges that contradicts the often held view that such colleges are established merely for monetary benefits.